Características dos sistemas de produção de leite na região dos Campos Gerais do Paraná em propriedades de agricultura familiar - Tonet, Rosa Maira (2016)
Milk production stands out in the landscape of the global family farming in most countries and also in Brazil, the milk is produced by small farmers and small-scale, but statistics worldwide show reduction in the number of milk producing establishments, notably from small producers. In this scenario, on many points of weakness of family dairy farmers farmers, how they behave, what adjustments are needed to continue the activity. And yet, how to build a production system that has a great performance without increasing their risks, and what capacity they have to reduce losses with potential risks, including the ability to plan and program strategies related to reducing its degree of vulnerability. It is suggested that studies using the concept of vulnerability are carried out under the agriculture and livestock, aiming to delineate high risk points in the production, so that it can later develop effective policies and methodologies to reduce the degree of vulnerability of production systems, especially in the field of family farming. The aim of this study was to characterize milk production systems in the municipalities of Carambeí, Castro and Ponta Grossa in the state of Parana, Brazil, by identifying the strengths and weaknesses of small farmers operations. A total 60 producers were interviewed between March and May 2015 (20 in each municipality). The two criteria required to participate in this study were that dairy was the main source of income and that the operation be family farm. The statistical methods used were principal component analysis (PCA) and bottom up hierarchical cluster analysis (HCA). The CP1 variables were the number of animals/family-based cell, liters/cow/day, use of haylage and liters/family-based cell, which had a 24.64% total variance. The CP2 variables were use of silage shredders, type equipment and purpose of the equipment, wich had a 22.56% total variance. The CP3 variables milk production/hectare, bonus for milk quality, the amount paid per liter of milk and destination of production, which had 20.11% total variance. The 60 operations produced six clusters. We were unable to apply the concept of vulnerability in its entirety. As a result, we used fragility and strength.